The efficiency of a Swoxid prototype and an antimicrobial nanofiber membrane as POU filters - Gaborone, Mamosete Dorothy (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.